(untitled) (Wudil Journal of Science and Technology Education, 2025)
Field trials were conducted at Aliko Dangote University of Science and Technology, Wudil Teaching and Research Farm, Gaya, Kano State (Latitude: 11.9331° N, Longitude: 8.5216° E), to study the growth, yield and Nodulation of some soybean varieties in Sudan Savannah Agro- ecological zone of Nigeria. The treatments consisted of nine soybean varieties (TGX 1448-2E, 1987-10E, 1740-1F, 1987-62F, 1904-6F, 1951-3F, 1945-1F, 1835-10E, 1955-4F). These were laid out in a randomized complete block design and replicated fourtimes. Data collected included Canopy Height, Number of Branches, Canopy Spread, Nodulation, Number of Pods per Plant, Number of Seeds per Pod, 100 Seeds Weight, Haulm fresh weight, Haulm Dry Weight and Grain Yield per hectare. The data were analyzed using Analysis of Variance and means separated by Duncan Multiple Range Test (DMRT) at 5% level of probability using GenStat statistical package. The result of the investigation revealed that variety significantly affected growth, yield and nodulation characters studied. The greatest yield per hectare was produced by TGX 1740-1F and TGX 1904-6F which were statistically similar. While the least was obtained by TGX 1945- 1F. In conclusion, two soybean varieties TGX 1740-1F and TGX 1904-6F were identified for greater grain and Stover yield at Gaya.